Clean and sustainable environment problems in forested areas related to recreational activities: case of Lithuania and Turkey - Atalay, Ahmet; Perkumiene, Dalia; Aleinikovas, Marius; Škėma, Mindaugas (Frontiers in Sports and Active Living, 2024)
Introduction With the acceleration of social life, people's interest and demand for forestry recreation activities is increasing. However, with this increase, it is inevitable that negative environmental effects will occur. Particularly mass participation poses an important risk for environmental sustainability. In this context, the aim of this study is to determine the recreational activities organized in forest areas in Turkey and Lithuania, the environmental effects of these activities and the precautions to be taken. Methods In Turkey and Lithuania, interviews were conducted to determine the attitudes of experts involved in recreational activity processes towards a clean environment and environmental sustainability. A semi-structured interview form was used in the interviews with forest operators and other experts. The sample group of the research consists of 17 experts from Turkey and Lithuania. Results According to the results of the research, recreational activities are organized in forest areas in both countries, but the most important problem related to these activities is waste production. In addition, there is also damage to the natural environment. Although there are legal regulations in both countries, there are no definite results in solving environmental problems. Conclusions It can be said that necessary measures such as raising awareness of people and ecological education should be taken in order to ensure the right of individuals to live in a safe and clean environment and at the same time to ensure sustainability in forest areas. as the improvement of legal regulation.